2022
DOI: 10.1038/s12276-022-00849-2
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin negatively modulates mechanical stress-mediated ligamentum flavum hypertrophy through TGF-β1 signaling

Abstract: Ligamentum flavum hypertrophy (LFH) is a major cause of lumbar spinal canal stenosis (LSCS). The pathomechanisms for LFH have not been fully elucidated. Isobaric tags for relative and absolute quantitation (iTRAQ) technology, proteomics assessments of human ligamentum flavum (LF), and successive assays were performed to explore the effect of clusterin (CLU) upregulation on LFH pathogenesis. LFH samples exhibited higher cell positive rates of the CLU, TGF-β1, α-SMA, ALK5 and p-SMAD3 proteins than non-LFH sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…We found that the activation of fibroblasts by M2 macrophages is significantly weakened after the sequence mutation, and even overexpression of SP1 cannot reverse this effect. However, exogenous TGF-β1 (5 ng/mL) 22 can significantly increase the activity of fibroblasts ( Figures 3 G and S5 A). Even with overexpression of SP1, mutation of the TGF-β1 BE1 sequence in M2 macrophages can significantly reduce the migration efficiency of fibroblasts, which is reversed by exogenous TGF-β1 ( Figures 3 H and S5 B).…”
Section: Resultsmentioning
confidence: 97%
“…We found that the activation of fibroblasts by M2 macrophages is significantly weakened after the sequence mutation, and even overexpression of SP1 cannot reverse this effect. However, exogenous TGF-β1 (5 ng/mL) 22 can significantly increase the activity of fibroblasts ( Figures 3 G and S5 A). Even with overexpression of SP1, mutation of the TGF-β1 BE1 sequence in M2 macrophages can significantly reduce the migration efficiency of fibroblasts, which is reversed by exogenous TGF-β1 ( Figures 3 H and S5 B).…”
Section: Resultsmentioning
confidence: 97%
“…The development of LFH is affected by many factors, including mechanical stress, age, sex, obesity and diabetes mellitus; however, the specific mechanism has not yet been completely clarified 11 , 14 , 33 , 34 . A variety of studies have shown that the development of LFH is closely related to fibrosis, and multiple cell factors participate in this process, among which TGF-β1 is known to be crucial in the development of LFH pathology 4 , 7 , 11 , 13 18 , 35 , 36 . In the present study, the bioinformatic analysis and in vivo and in vitro experiments again emphasize this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TGF‐β1 has been investigated in various fibrosis-associated pathological processes, including lung and kidney fibrosis, joint contracture, scar repair, liver cirrhosis, postoperative epidural adhesions, and atherosclerosis 22 , 23 , 25 , 35 , 37 39 . TGF‐β1 can activate the TGF‐β1/Smad3 pathway, thereby regulating the differentiation from fibroblasts to myofibroblasts though the upregulation of α-SMA 23 , 35 , 36 . In addition, TGF-β1 can induce the synthesis of multiple ECM components, including collagen I, collagen III, and fibronectin 23 , 36 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we screened four senescence-related genes ( MALT1 , ENO1 , CLU , and LDHB ) by comparing the lists of DEGs and SRGs, and validated the expression of CLU by western blot analysis. CLU is a conserved heterodimeric sulfated glycoprotein [ 48 ]. It was reported that CLU could regulate the expressions of SASP components (e.g., IL-6 and IL-8) through protein kinase B [ 49 ], Nfkb [ 50 ], or p38 mitogen-activated protein kinase (p38MAPK) pathways [ 51 ].…”
Section: Discussionmentioning
confidence: 99%